Analysis of Green Industry Practice Implementation in Operational Management: Motivations, Barriers, and Institutional Impacts - Raditya Surya Putra; Novia Kartika Sari; Eko Prasetyo Wibowo (Publika Bersama Nusantara, 2026)
This study investigates the implementation of green industry practices within manufacturing operational management, with a particular focus on the motivational drivers that prompt adoption, the barriers that impede scaling, and the institutional impacts that result from sustained environmental stewardship. Employing a qualitative research design grounded in multiple case study methodology and institutional theory, data were collected through in-depth interviews with 36 key informants spanning operations directors, environmental managers, process engineers, supply chain specialists, and regulatory officers across six manufacturing facilities representing diverse industrial sub-sectors. Data collection was complemented by non-participant field observations and systematic document analysis of sustainability reports, environmental audit records, and operational policy documentation. Thematic analysis identified seven motivational driver categories ranging from regulatory compliance and market access imperatives to intrinsic leadership values and enterprise risk management alongside six classes of implementation barriers encompassing financial, technical, organizational, cultural, regulatory, and supply chain dimensions. The study further maps the institutional impacts of green practice adoption across six stakeholder dimensions: regulatory relationships, investor relations, customer legitimacy, community license to operate, industry peer positioning, and human capital. An integrative Green Industrial Operations (GIO) model is proposed, providing a structured pathway for manufacturing organizations to transition from compliance-driven to value-driven environmental management. Findings contribute to the green management and industrial operations literature by foregrounding the institutional and relational dimensions of environmental practice that operational metrics alone fail to capture.